Battling over Jobs: Occupational Licensing in Health Care - Kleiner, Morris M. (American Economic Review, 2016)
The goal of this paper is to outline the major tensions between the monopoly face of licensing versus potential consumer protection goals of occupational regulation in the health care industry. Historically, health care occupations limited supply as a method of raising earnings, but with the growth in the number of newly regulated occupations, many professions have come in conflict over who gets to do the work. Rather than having consumers decide, state legislatures and licensing boards determine the allocation of tasks. The paper outlines policies that may allow consumers rather than service providers determine the direct allocation of these jobs.